Faktor-faktor yang mempengaruhi pendapatan rumah tangga miskin di Kota Jambi - Eriyadi, Eriyadi; Yulmardi, Yulmardi; Heriberta, Heriberta (Jurnal Paradigma Ekonomika, 2021)
Jambi City has several impoverished residents, which is counted 16.632 with the family head. 1) The purpose of this study is to analyze the characteristics of social and economic income of poor household heads in Jambi city 2) Analyzing the influence of education level, type of work, and the number of dependents significantly partially affect the income of poor household heads in Jambi City. With data primary and analyze descriptive and double regression. The results of this study are the level of education, type of work, and the number of simultaneously significant effects on the income of poor heads of households. The level of education, the type of work, and the number of dependents partially have a positive and significant impact on the income of poor household heads. The most dominant independent variables affecting the income of poor household heads in Jambi City are the dependent variable variables. Â